2021
DOI: 10.5194/acp-21-1049-2021
|View full text |Cite
|
Sign up to set email alerts
|

The CLoud–Aerosol–Radiation Interaction and Forcing: Year 2017 (CLARIFY-2017) measurement campaign

Abstract: Abstract. The representations of clouds, aerosols, and cloud–aerosol–radiation impacts remain some of the largest uncertainties in climate change, limiting our ability to accurately reconstruct past climate and predict future climate. The south-east Atlantic is a region where high atmospheric aerosol loadings and semi-permanent stratocumulus clouds are co-located, providing an optimum region for studying the full range of aerosol–radiation and aerosol–cloud interactions and their perturbations of the Earth's r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
68
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 140 publications
3
68
0
Order By: Relevance
“…Keil and Haywood, 2003). While lidar retrievals of aerosols above cloud have been available for some time from the active CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization) instrument (Hu et al, 2007;Chand et al, 2008;Liu et al, 2015), retrievals of aerosols from passive instrumentation have also been developed. Studies based on the OMI (Ozone Monitoring Instrument; Torres et al, 2012; de Graaf et al, 2019), SCIAMACHY (SCanning Imaging Absorption SpectroMeter for Atmospheric CHar-tographY; de Graaf et al, 2012), MODIS (MODerate resolution Imaging Spectroradiometer; Jethva et al, 2013;Meyer et al, 2015;Sayer et al, 2016) and POLDER (POLarization and Directionality of the Earth's Reflectances; Waquet et al, 2013;Peers et al, 2015) satellite instruments have already demonstrated the potential of retrieving both cloud properties and above-cloud aerosol optical thickness (AOT) from passive sensors or deriving the direct radiative effect of aerosols above clouds.…”
Section: Introductionmentioning
confidence: 99%
“…Keil and Haywood, 2003). While lidar retrievals of aerosols above cloud have been available for some time from the active CALIOP (Cloud-Aerosol Lidar with Orthogonal Polarization) instrument (Hu et al, 2007;Chand et al, 2008;Liu et al, 2015), retrievals of aerosols from passive instrumentation have also been developed. Studies based on the OMI (Ozone Monitoring Instrument; Torres et al, 2012; de Graaf et al, 2019), SCIAMACHY (SCanning Imaging Absorption SpectroMeter for Atmospheric CHar-tographY; de Graaf et al, 2012), MODIS (MODerate resolution Imaging Spectroradiometer; Jethva et al, 2013;Meyer et al, 2015;Sayer et al, 2016) and POLDER (POLarization and Directionality of the Earth's Reflectances; Waquet et al, 2013;Peers et al, 2015) satellite instruments have already demonstrated the potential of retrieving both cloud properties and above-cloud aerosol optical thickness (AOT) from passive sensors or deriving the direct radiative effect of aerosols above clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The large uncertainty in aerosol climate forcing in the SE Atlantic was the impetus for the NASA ORACLES (ObseRvations of Aerosols above CLouds and their intEractionS) project, funded through the NASA Earth Venture Suborbital (EVS-2) program , as well as complementary campaigns (Zuidema et al, 2016;Formenti et al, 2019;Haywood et al, 2021). The ORACLES project explicitly measured aerosol properties necessary to calculate the direct aerosol radiative effect (DARE).…”
Section: Introductionmentioning
confidence: 99%
“…The WRF-CAM5 and GEOS models are included because they were used for aerosol and meteorological forecasting during the ORACLES campaign. Similarly, the UM-UKCA modeling team participated in the U.K. CLARIFY (Cloud-Aerosol-Radiation Interactions and Forcing) campaign, which deployed out of Ascension Island (Figure 1) in 2017 (Haywood et al, 2021). In 2016 both ORACLES and the French AEROCLO-SA (AEROsol radiation and CLOuds in 110 Southern Africa; Formenti et al, 2019) campaign deployed out of Walvis Bay, Namibia, with the latter focusing on nearcoast aerosols.…”
Section: Introductionmentioning
confidence: 99%
“…The ORACLES campaign looks into aerosol-cloud interactions over the southeast Atlantic throughout the majority (August 2017, September 2016 and October 2018) of the biomass burning season (Zuidema et al, 2016;Cochrane et al, 2019;Pistone et al, 2019). CLouds and Aerosol Radiative Impacts and Forcing for Year 2017 (CLARIFY-2017) aimed to better represent the radiative and microphysical properties of stratocumulus clouds as they transition to cumulus clouds (Haywood et al, 2021).…”
Section: Introductionmentioning
confidence: 99%